Liposomal formulations loaded with a eugenol derivative for application as insecticides: encapsulation studies and In silico identification of protein targets - Fernandes, Maria José Gomes (2022)
Supplementary Materials can be downloaded at: https://www.mdpi.com/article/10.3390/nano12203583/s1,